Mobile Banking Bank Nagari Menurut Persepsi Mahasiswa Perbankan Syariah UIN Mahmud Yunus Batusangkar - Vicy Andriany; Nofiara Kurnia Putri (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
The problem in this study is many students in Islamic Banking don’t use Nagari Bank Mobile Banking application,even though many people in general have used the Nagari Mobile Banking application which provides a lot of convenience in transactions. The purpose of this study was to determine how the perception of Islamic banking students on the use of mobile banking at Bank Nagari. The type of research is field research, namely with a quantitative descriptive approach. Collection technique is a questionnaire distributed to students of Islamic Banking class 2016, 2017, and 2018. The population consists of 180 Islamic Banking students and a sample of 64 students. Analysis technique is using the Guttman scale. The results of the study can be concluded that the use of Nagari Bank mobile banking in Islamic Banking students choosing not to use more than those using the Nagari Mobile Banking application. The perceptions of students who use and do not use Bank Nagari's mobile banking are different which can be seen from the perception indicators, namely absorption of stimuli or objects from outside the individual, understanding and understanding, assessment or evaluation.factors that influence students to choose or not to use mobile banking at Bank Nagari, namely internal factors and external factors.